Governance as co-production of public services - Sześciło, Dawid (Journal of Public Governance, 2015)
The idea of co-production is the result of the application of governance theory to the organization of public service delivery. This paper presents the genesis of the concept of co-production of public services, and, on the basis of a review of international literature, it describes the current state of the debate on the benefits of co-production, factors stimulating its development, as well as constraints, challenges and potential risks associated with its dissemination. In summary, the author attempts to construct a comprehensive definition of co-production, paying special attention to the elements distinguishing it from the two dominant paradigms of public service delivery – the statist and the market-based model.